MEASURES IMPLEMENTED IN THE INDUSTRY OF THE SURKHANDARYA OASIS AND THEIR CONTRIBUTION TO THE DEVELOPMENT OF THE INDUSTRY (IN THE YEARS OF INDEPENDENCE) - Muzrabov Yorqinjon To’xtamurot o’g’li (American Journals, 2023)
The purpose of this article is to scientifically and historically illuminate the essence of the policy of the government of the Republic of Uzbekistan aimed at establishing world-class industrial enterprises in the Surkhandarya oasis during the years of independence.
Keywords: light industry, heavy industry, cotton ginning points, yarn spinning.